THE EFFECT OF MUROTTAL AL-QUR'AN THERAPY ON CHANGES IN ANXIETY IN THE ELDERLY WITH HYPERTENSION IN THE KALIKOTES HEALTH CENTER WORK AREA - Agustina, Lusinta; Suryani, Emy; Aurellia, Tita (RADJA PUBLIKA, 2025)
Hypertension has become a global health problem as well as one of the leading causes of death that occurred suddenly so often called